2002
DOI: 10.1139/x01-198
|View full text |Cite
|
Sign up to set email alerts
|

Geographical variation in random amplified polymorphic DNA and quantitative traits in Norway spruce

Abstract: Quantitative traits and random amplified polymorphic DNA variations were investigated on the whole natural range of Norway spruce (Picea abies (L.) Karst.). Results showed that the species can be separated into two main groups (northern and central Europe) using both types of characters. Such spatial and geographical fragmentation of species natural range rarely occurs in conifers and is consistent with prolonged geographical isolation within two refugial zones located in distinct environmental conditions (Mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
46
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 35 publications
16
46
1
1
Order By: Relevance
“…The mean value of expected heterozygosity of Norway spruce tested in IPTNS-IUFRO 1964/68 experiment in Krynica was almost two times lower (H e = 0.14) compared to the previously estimated for the Baltic-Nordic (H e = 0.283), Hercine-Carpathian (H e = 0.279) and Alpine (0.288) provenances (Collignon et al 2002) as well as for the Polish populations (H e = 0.298) (Nowakowska et al 2006). The observed differences may probably result from the analysis of different loci and may result from the specific nature of the investigated population (provenience experiment analysing the progeny of spruce from the entire range of the species).…”
Section: Variability Of Growth Features and Genetic Polymorphismcontrasting
confidence: 55%
“…The mean value of expected heterozygosity of Norway spruce tested in IPTNS-IUFRO 1964/68 experiment in Krynica was almost two times lower (H e = 0.14) compared to the previously estimated for the Baltic-Nordic (H e = 0.283), Hercine-Carpathian (H e = 0.279) and Alpine (0.288) provenances (Collignon et al 2002) as well as for the Polish populations (H e = 0.298) (Nowakowska et al 2006). The observed differences may probably result from the analysis of different loci and may result from the specific nature of the investigated population (provenience experiment analysing the progeny of spruce from the entire range of the species).…”
Section: Variability Of Growth Features and Genetic Polymorphismcontrasting
confidence: 55%
“…Indeed, these species generally show well-marked local adaptations that often find their expression in heritable traits as cold hardiness or bud set sensitivity to photoperiod (e.g. [10,19,23]). Yet, in such long-lived organisms with late reproductive maturity, the number of generations that occurred during the post-glacial expansion that followed the preboreal period (around 10 000 to 9 000 BP in Europe) does probably not exceed one hundred [26].…”
Section: Introductionmentioning
confidence: 99%
“…The low correlation between locations is shown in many terrestrial pants such as tropical evergreen tree (Li et al 2008), barley (Lund 2002), and potato (Veteläinen et al 2005) and may be explained by the different molecular markers and morphological characteristics (Collignon et al 2002, Navarro et al 2005. Molecular markers are usually considered selectively neutral (Strauss et al 1992) been observed to vary, likely in response to seawater temperature (see reviews in Serisawa et al 2002a).…”
Section: Discussionmentioning
confidence: 99%